The Duodenal Microbiota Composition of Adult Celiac Disease Patients Is Associated with the Clinical Manifestation of the Disease - Wacklin, Pirjo; Kaukinen, Katri; Tuovinen, Elina; Collin, Pekka; Lindfors, Katri; Partanen, Jukka; Mäki, Markku; Mättö, Jaana (Inflammatory bowel diseases, 2013)
Celiac disease is classically manifested in the gastrointestinal (GI) tract but extraintestinal symptoms, such as dermatitis herpetiformis (DH), are also common. Besides several well-known shared genetic risk factors and an environmental trigger, gliadin, factors determining the clinical outcome of the disease are not known. In this study, the role of duodenal microbiota in the celiac disease outcome was studied by analyzing mucosa-associated microbiota in celiac disease patients with a variety of intestinal and extraintestinal symptoms.MethodsMicrobiota in duodenal biopsy samples obtained from 33 patients with celiac disease with GI, DH, anemia, or mixed symptoms, as well as screen-detected asymptomatic celiac disease and 18 control subjects were analyzed using PCR denaturing gradient gel electrophoresis and a subset of samples additionally by the 16S ribosomal RNA gene sequencing.ResultsThe composition and diversity of mucosal microbiota was associated with the manifestation of celiac disease when analyzed using PCR denaturing gradient gel electrophoresis and the 16S ribosomal RNA gene sequencing. The patients with celiac disease with GI symptoms or anemia had lower microbial diversity than those with DH. Moreover, the patients with GI symptoms had different intestinal microbiota composition and structure, dominated by Proteobacteria, in comparison to those with DH or control subjects (patients with dyspepsia). The relatively similar intestinal microbiota composition in the control subjects and those with DH was characterized by the high abundance of Firmicutes.ConclusionsThe two common outcomes of celiac disease, classical GI and extraintestinal manifestations, had marked differences on the diversity and composition of intestinal microbiota. This association suggested that intestinal microbiota may have a role in the manifestation of the disease.